2010
DOI: 10.1380/ejssnt.2010.112
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Nanorefractory Dimetaloxide Spinel

Abstract: The aim of this work consists of synthesis of nanocrystalline single-phase MgAl2O4 powders from comparatively less expensive raw materials and simple methods. We have used conventional heating in two different chemical routes, co-precipitation and combustion methods. In the first procedure combination of precipitation and gelation process is used to prepare spinel from aluminum and magnesium sulfates. The other involved a rapid evaporation of polyvinyl alcohol (PVA) that added to a mixed metal nitrate solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Indeed, the value of d has clearly been shown to be dependent on the chosen synthesis route. Routes included the solid-state reaction, [20][21][22] tartaric complex formation as the oxide precursor, 23 a microwave-assisted hydrothermal process, 24 autocombustion using glycine/urea fuels, 14,25 sol-gel, 11 or the Pechini route. 8,26 Special care must be taken with the type of synthesis precursors and the accessible crystallite sizes as they can both affect the inversion rate of the as-prepared samples.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the value of d has clearly been shown to be dependent on the chosen synthesis route. Routes included the solid-state reaction, [20][21][22] tartaric complex formation as the oxide precursor, 23 a microwave-assisted hydrothermal process, 24 autocombustion using glycine/urea fuels, 14,25 sol-gel, 11 or the Pechini route. 8,26 Special care must be taken with the type of synthesis precursors and the accessible crystallite sizes as they can both affect the inversion rate of the as-prepared samples.…”
Section: Introductionmentioning
confidence: 99%
“…31 Hence, it is very interesting to gauge the effect of different synthetic processes on the cationic distribution. Many synthetic routes to pure ZnAl 2 O 4 of various particle size have been reported in the literature, such as solid-state reactions, [32][33][34] tartaric complex formation as the oxide precursor, 35 microwave-assisted hydrothermal processes, 36 autocombustion using glycine/urea fuels, 37,38 sol-gel methods 27 and the Pechini route. 39,40 In this paper, the co-precipitation technique and the Pechini route with various final thermal treatments are compared, and the correlation of the luminescence properties of ZnAl 2 O 4 to its structure (inversion rate, presence of defects) is investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Because it has been demonstrated that the inversion rate is strongly linked to the experimental conditions [16][17][18][19][20], we propose here to use a Pechini synthesis to have access to a large crystallite size distributio n to impact the  ratio [3]. To control the inversion factor of doped ZnAl 2 O 4 materials may be of great interest especially when the luminescent properties are affected by the location of the emitting center, the crystal field strength .…”
Section: Color Switch Due To Luminescent Cation Migration [23]mentioning
confidence: 99%